2022
DOI: 10.4081/jphr.2022.2803
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia is a Determinant of Early Death in the Long-Term Course of Post-Myocardial Infarction

Abstract: Among people with ST-segment elevation myocardial infarction (STEMI), high alexithymia was associated with delay to hospital arrival. High alexithymia could be a determinant of early death in the long term after STEMI. People with STEMI who participated in a survey in 2011, was tested about the state of life in 2021. The sample was divided into two cohorts (cut-off: TAS-20≥61 in 2011). The relationship between possible death occurred and having high alexithymia was calculated by comparing the mortality after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These studies were not included in our review because the patient diagnoses were self-reported, so they did not meet the inclusion criteria, even if they add further empirical evidence to our findings. With reference to the relationship between alexithymia and medical conditions, Carta et al (2022) reported that this variable is associated with an increased risk of death in a long-term course of myocardial infarction. Such an association may be due to a delay in requesting help, depending on the difficulty of the early identification of the typical symptoms of a heart attack.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were not included in our review because the patient diagnoses were self-reported, so they did not meet the inclusion criteria, even if they add further empirical evidence to our findings. With reference to the relationship between alexithymia and medical conditions, Carta et al (2022) reported that this variable is associated with an increased risk of death in a long-term course of myocardial infarction. Such an association may be due to a delay in requesting help, depending on the difficulty of the early identification of the typical symptoms of a heart attack.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recently, a 10-year longitudinal study among a cohort of 83 people with ST-segment elevation myocardial infarction (STEMI) found that high alexithymia was a significant determinant of early death in the long term after STEMI [Log Rank Mantel-Cox ¼ 6.899, 1 df, P ¼ 0.009; RR ¼ 5.75; 95% confidence interval (CI) 1.116-29.637] without any differences regarding age, sex, high alexithymia between individuals on whom it was possible to verify the state in life and in whom it was not. 21 These data are hypothesis-generating, and more research is needed to establish the relation between high levels of alexithymia and death in people with prior AMI.…”
Section: Instruments To Identify and Measure Alexithymiamentioning
confidence: 99%
“…Risk factors of non-communicable diseases include behavioral, psychological, and biological. Findings of various studies show that psychological and behavioral risk factors, along with biological risk factors, have an effect on the incidence and progression of MI, which should be given special attention in prevention programs [ 11 , 12 ]. In recent years, the risk factors for non-communicable diseases such as smoking, obesity, high blood pressure, inadequate physical activity, and consumption of inappropriate foods, all rooted in poor lifestyle, have also increased in Iran [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%